Teungku Dayah: Aplikasi Metode Dakwah Dalam Membentuk Akhlaq Santri - Paisal, Jon (BINA' AL-UMMAH, 2021)
People morality in social life today make us very concerned, almost every social media reports various public actions that are not in line with religious and cultural norms; such as consuming alcohol, drug parties, online gambling, corruption, fraud, and murder. The irony is that some of the perpetrators are educated people, who commit acts of uneducated people. In this case, formal and non-formal educational institutions need to evaluate their education system and use the right method. Da'wah activities through quranic recitations conducted in Dayah or Islamic boarding schools can play a role in the formation of human morals if it carried out by using the right method. Historically, the Da'wah carried out by the Prophet Mohammad was very effective in carrying out moral transformation because of the effective methods and approaches. This study aims to determine the da'wah of Tengku Dayah in shaping the morals of students in Dayah Darul Muta'alimin, Seuneubok village, Johan Pahlawan district, West Aceh district. This research was conducted using a qualitative descriptive approach, data collection techniques through interviews, documentation and observation. The results showed that the da'wah of Teungku Dayah Darul Muta'alimin in shaping the morals of students through: The method of habituation of memorizing the Qur'an, the method of da'wah through regular recitations, exemplary methods, worship practice methods. Santri (moslem students) are educated through various methods in order to become a generation with virtuous character, noble character, faithful and obedient to the teachings of Islam.